Allo-polyherbal Approaches for Managing Metabolic Syndrome: A Narrative Review - Sharma, Pratiksha; Singh, Varinder; Baldi, Ashish (Natural Products Journal, The, 2024)
Metabolic syndrome (MS) represents a complex cluster of medical conditions with profound implications for global public health. This constellation of disorders substantially increases the susceptibility to type 2 diabetes, obesity, thrombosis, cardiovascular disease, and hyperlipidemia. The drugs currently prescribed for managing MS offer limited efficacy, likely due to their limited scope of action. Owing to their restricted mechanisms of action, these medications often lead to significant side effects such as weight gain, bone marrow impairment, Raynaud's phenomenon, galactorrhea, and others. Consequently, these adverse effects contribute to poor patient adherence and restrict the overall effectiveness of the treatment. Thus, developing new therapeutic strategies for managing MS is certainly required. Recent investigations have been concentrated on formulating strategies that combine conventional synthetic drugs with herbal medicines (which act via multiple targets), aiming to enhance treatment efficacy and enhance patient adherence in the management of MS. This concept of combining synthetic and herbal drugs is termed ‘Allo-polyherbal’ and has been shown to improve the efficacy of synthetic drugs and reduction of adverse effects. The present review uncovers the concept of Allo-polyherbal and reveals the potential benefits of using Allopolyherbal in managing diabetes, cardiovascular, hypertension, hyperlipidemia, obesity, and thrombosis leading to MS.
Keywords: hypertension